Neutron Generated during Proton Bombardment in Water Molecule - Gusti Atika Urfa; Nurma Sari; Amar Vijai Nasrulloh (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Proton therapy is a treatment modality which can deliver dose precisely to cancer tumor in comparison to photon therapy, However, study about the biological effect of proton therapy are not well known. In this study, simulation of proton bombardment with energy 110 MeV to water is conducted using Geant4 software. The selection of water as the object of proton bombardment due to majority of human body is consisted of water. Water molecule in this simulation is a cube shaped with 10 x 10 x 10 cmand surrounded by PMMA material with 0.5 cm thickness. From the simulation results, it can be seen that <2% neutrons particle are formed due to the interaction of proton particles with water material. Small dose of neutron can be dangerous for body because it has high biological effectiveness and thus even a small absorbed dose might cause negative side effects in the patient.